2022
DOI: 10.3390/molecules27238636
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antifungal Activity of Zanthoxylum armatum Fruit Essential Oil against Phytophthora capsici

Abstract: Pathogenic plant oomycetes cause devastating damage to fruits and vegetables worldwide. Plant essential oils (EOs) are known to be promising candidates for the development of fungicides. In this study, we isolated twelve EOs from Tetradium ruticarpum, Tetradium daniellii, Tetradium fraxinifolium, Zanthoxylum armatum, Ruta graveolens, and Citrus medica leaves and fruits. We then investigated their chemical composition and antifungal activity against phytopathogenic oomycetes. Our results demonstrated that Z. ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Several plant extracts exert antifungal functions by acting directly or indirectly on the cell membrane and cell wall of fungi, destroying the permeability of the cell membrane, damaging the integrity of the cell wall, and leaking important cell components. 27,29 Given the satisfactory antifungal activity of rhein against P. capsici, the antifungal mechanism of rhein was further investigated in this study. We found that rhein could severely affect the permeability and damage the integrity of the cell membrane, resulting in reduced membrane transport.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several plant extracts exert antifungal functions by acting directly or indirectly on the cell membrane and cell wall of fungi, destroying the permeability of the cell membrane, damaging the integrity of the cell wall, and leaking important cell components. 27,29 Given the satisfactory antifungal activity of rhein against P. capsici, the antifungal mechanism of rhein was further investigated in this study. We found that rhein could severely affect the permeability and damage the integrity of the cell membrane, resulting in reduced membrane transport.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results showing damage to the cell wall integrity have been reported in Geotrichum citri-aurantii treated with peppermint essential oil or P. capsici treated with euphorbia factor L 3 . 28,29 Moreover, the OM and TEM results indicated that the morphology and ultrastructure of mycelia were altered after treating P. capsici with rhein. These morphological changes could be attributed to the increased membrane permeability, resulting in the leakage of small molecules and increased membrane lipid peroxidation, thus accelerating cell death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… suppresses antigen-induced lymphocyte activation The composition of essential oil from fruit of the plant grown in Kagoshima, Japan/Yamaguchi, Japan: α-Pinene 1.78/1.18 β-Myrcene 2.97/3.54 Limonene 60.30/71.34 β-Phellandrene 8.22/7.27 α-Terpinene 5.12/5.51 p-Cymene 6.08/3.56 γ-Elemene 1.93/- α-terpineol -/1.90 (E,E)-α-farnesene -/1.00 [ 127 , 154 , 155 ] 11. Euodia ruticarpa ( E. ruticarpia ) (Rutaceae) It exhibits anticancer propeties by: increasing the level of IL-1β, TNF-α, IL-6 and IL-10 secreted by macrophages affecting regulation of Th1 (IL-2) and Th2 (IL-10) cytokines production by splenocytes activating NK cells and B cells The composition of essential oil from leaf /fruit: β-myrcene 31.03/38.14 β-phellandrene 18.38/25.89 trans-β-ocimene 3.35/- β-ocimene 3.21/17.82 (E)-4,8-dimethyl-1,3,7-nonatriene 6.17/- caryophyllene 2.21/- E-nerolidol 21.79/- γ-eudesmol 1.09/- β-eudesmol 1.52/- α-eudesmol 2.1/- α-pinene -/1.63 trans-β-ocimene -/12.29 [ 32 , 130 , 131 , 132 , 133 , 134 , 135 , 156 ] 12. Eucalyptus plant (Myrtaceae) Its topical application inhibits edema and enhances vascular permeability in IgE-mediated allergic dermatitis it may stimulate the immune function of the respiratory tract, improves phagocytic activity of macrophages and it can be used as an adjuvant in some infections and inflammatory diseases.…”
Section: Influence Of Selected Essential Oils On the Immune Systemmentioning
confidence: 99%
“…Conjointly, EOs are regularly more effective for preventive applications (i.e., applied before inoculation) than for curative uses (i.e., applied after inoculation) [121][122][123]. These two modes of application clearly target two opposing but complementary stages of the disease.…”
Section: Insights Of Essential Oils Activity On P Infestansmentioning
confidence: 99%